Nutritional Status as A Predictor of Surgical Outcomes in Adult General Surgery Patients - Muhammad Javed Khan, Asif Imran, Asfandyar Khan, Muhammad Mubassir, Sajjad Hussain, Zarka Sarwar, Huma Shafi, Tanzeela Nawaz, Rabia Jadoon (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Preoperative nutritional risk is common among surgical patients and may impair immune function, collagen synthesis, wound healing and tolerance of surgical stress. Nutritional risk can be identified through simple clinical screening and may help stratify patients who require closer perioperative monitoring and targeted nutritional support2,3,4. Objective: To evaluate whether preoperative nutritional risk predicts adverse postoperative outcomes among adult general surgery patients. Methods: This prospective cohort study was conducted in the Department of General Surgery at Mardan Medical Complex, Mardan, Pakistan, from January 2023 to April 2023. Adult general surgery patients undergoing operative management were categorized as having normal nutritional status or nutritional risk using a pragmatic assessment incorporating body mass index, serum albumin, unintentional weight loss, reduced oral intake and a nutrition-risk checklist. The primary outcome was 30-day postoperative complication rate. Secondary outcomes included surgical-site infection, delayed wound healing, hospital stay and readmission. Results: A total of 135 patients were included, comprising 88 patients with normal nutritional status and 47 patients at nutritional risk. Nutritionally at-risk patients were older, had lower BMI and had a higher proportion of albumin below 3.5 g/dL. Postoperative complications, surgical-site infection, delayed wound healing and median hospital stay were significantly higher in the nutritional risk group. Nutritional risk remained independently associated with postoperative complications with adjusted OR 2.55, 95% CI 1.13-5.75, p=0.024. Conclusion: Preoperative nutritional risk independently predicts adverse postoperative outcomes in adult general surgery patients. Routine nutrition screening and targeted perioperative nutrition pathways should be integrated into surgical admission and postoperative care. Keywords: nutritional risk; malnutrition; general surgery; postoperative complications; surgical-site infection; wound healing; prospective cohort study.